2019
DOI: 10.1039/c9cp00826h
|View full text |Cite
|
Sign up to set email alerts
|

Pd local structure and size correlations to the activity of Pd/TiO2 for photocatalytic reforming of methanol

Abstract: The interaction between Pd and TiO2 for promoting photocatalytic activity was investigated by tailoring the size of Pd nanoparticles and monitoring the photocatalytic activity of methanol photo-reforming reaction for hydrogen gas production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…At lower inlet reactant temperatures, the MSR reaction is relatively moderate without the temperature dropping significantly, and the "cold spot" appears at about 25 mm. At the lower inlet reactant temperature, the MSR reacts relatively gently without the temperature dropping significantly, so the "cold spot" is not observed.The "cold spot" temperature difference is smaller than that of the literature [28,29] because a microreator coupled with catalyst coating which has advantages of efficient heat transfer is adoptd in this study. Most of the reaction is completed at about 70 mm, after which the temperature increases rapidly.…”
Section: Effects Of Reactant Inlet Temperature On Msrmentioning
confidence: 93%
See 2 more Smart Citations
“…At lower inlet reactant temperatures, the MSR reaction is relatively moderate without the temperature dropping significantly, and the "cold spot" appears at about 25 mm. At the lower inlet reactant temperature, the MSR reacts relatively gently without the temperature dropping significantly, so the "cold spot" is not observed.The "cold spot" temperature difference is smaller than that of the literature [28,29] because a microreator coupled with catalyst coating which has advantages of efficient heat transfer is adoptd in this study. Most of the reaction is completed at about 70 mm, after which the temperature increases rapidly.…”
Section: Effects Of Reactant Inlet Temperature On Msrmentioning
confidence: 93%
“…The results showed that when the temperature difference between the cold and hot ends of the thermoelectric module was 22 K, the output voltage of the power chip was 55 mV, the methanol conversion was 72.6%, and the molar fraction of hydrogen was 62.6%.The packed bed is widely used for the conventional MSR method. However, the packed bed was reported to suffer from axial temperature gradients and cold spots [28,29]. These problems, which lead to thermal stresses in the channels, result from the severe limitations of mass and heat transfer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high cost and limited availability of Pt, Pd represents a viable alternative because of its lower cost and greater abundance than Pt [28]. Pd doped TiO 2 (Pd/TiO 2 ) has been actively investigated in photocatalysis especially for water splitting and biomass reforming [16,[28][29][30][31][32]. Luna et al reported a high photocatalytic activity for H 2 generation using a TiO 2 surface modified with Pd nanoparticles prepared by radiolysis [28].…”
Section: Pd/tiomentioning
confidence: 99%
“…However, the mechanistic studies using these alcohols for hydrogen evolution can provide important information on catalyst activity. Methanol in particular has been studied extensively in this regard [27,32,58,84,85].…”
Section: Alcoholsmentioning
confidence: 99%